Molecular Characterisation of Soybean Osmotins and Their Involvement in Drought Stress Response - Faillace, Giulia Ramos; Caruso, Paula Bacaicoa; Timmers, Luis Fernando Saraiva Macedo; Favero, Débora; Guzman, Frank Lino; Rechenmacher, Ciliana; de Oliveira-Busatto, Luisa Abruzzi; de Souza, Osmar Norberto; Bredemeier, Christian; Bodanese-Zanettini, Maria Helena (Frontiers in Genetics, 2021)
Osmotins are multifunctional proteins belonging to the thaumatin-like family related to plant stress responses. To better understand the functions of soybean osmotins in drought stress response, the current study presents the characterization of four previously described proteins and a novel putative soybean osmotin (GmOLPc). Gene and protein structure as well as gene expression analyses were conducted on different tissues and developmental stages of two soybean cultivars with varying dehydration sensitivities (BR16 and EMB48 are highly and slightly sensitive, respectively). The analyzed osmotin sequences share the conserved amino acid signature and 3D structure of the thaumatin-like family. Some differences were observed in the conserved regions of protein sequences and in the electrostatic surface potential. P21-like present the most similar electrostatic potential to osmotins previously characterized as promoters of drought tolerance in Nicotiana tabacum and Solanum nigrum. Gene expression analysis indicated that soybean osmotins were differentially expressed in different organs (leaves and roots), developmental stages (R1 and V3), and cultivars in response to dehydration. In addition, under dehydration conditions, the highest level of gene expression was detected for GmOLPc and P21-like osmotins in the leaves and roots, respectively, of the less drought sensitive cultivar. Altogether, the results suggest an involvement of these genes in drought stress tolerance.